Interpersonal Communication in Guidance and Counseling: The Role of Teachers' Empathy, Self-esteem, and Intrapersonal Peacefulness - Buchori, Sahril; Fakhri, Nurfitriany; Fakhri, Ria Andriany (Journal of Educational Science and Technology (EST), 2023)
The aim of the research is is to investigate the influence of empathy, self-esteem, and intrapersonal peacefulness on the development of interpersonal communication skills in teachers engaged in guidance and counseling. The study's sample comprises guidance and counseling teachers who are currently employed at the junior high school and high school levels within the South Sulawesi region. The participant pool for this research consisted of 74 teachers, who were selected by accidental sampling. The present study uses four specific scales: the Interpersonal Reactivity Index (IRI), the Rosenberg Self Esteem Scale (RSES), the Self Personal Scale (SPS), and the Interpersonal Communication Scale (ICS). The presence of empathy and intrapersonal peacefulness has the potential to act as indicators for improving interpersonal communication abilities among guidance and counseling teachers in South Sulawesi. Other findings derived from the data analysis indicate that there were no statistically significant disparities observed in the duration of employment among guidance and counseling teachers across various factors, including empathy, self-esteem, intrapersonal peacefulness, and interpersonal communication. Significant disparities in levels of empathy have been identified between those identifying as female and male. Research has shown that female guidance and counseling teachers exhibit higher levels of empathy compared to their male colleagues within the same professional field. This study is the initial research in Indonesia that aims to uncover the communication abilities of guidance and counseling teachers, focusing on their individual levels of peacefulness, empathy, and self-esteem. With an emphasis on peacefulness, it is anticipated that this research will serve as a foundation for the development of new training programs designed to enhance the communication abilities of guidance and counseling teachers.